Imperial Israel and the Palestinians : the politics of expansion - Masalha, Nur, 1957- (Pluto Press, 2000)
In Imperial Israel and the Palestinians, Nur Masalha provides a history of Israel's expansionist policies, focusing on the period from the June War of 1967 to the present day. He demonstrates that imperialist tendencies in Israel run the political gamut, from Left to Right. Masalha argues that the heart of the conflict between Zionist immigrants/settlers and the native Palestinians has always been about land, territory, demography and water. He documents how Israeli policy has made it a priority to expel the Palestinians, either by war or peaceful measures. But these imperialist tendencies are not restricted to extremist zealots. The author uncovers the expansionist policies found in Labour Zionism and Kookist ideology. Chapters cover the Whole Land of Israel Movement, Zionist Revisionism and the Likud Party, Gush Emunim and the religious fundamentalists, parties and movements of the far right and the evolution of Israeli Jewish public attitudes since 1967.
Keywords: Arab-Israeli conflict -- 1973-1993.; Arab-Israeli conflict -- 1993-; Zionism -- Israel.; Israel -- Politics and government.; Israel-Arab War, 1967 -- Occupied territories.; Israel -- Boundaries.; Conflit israélo-arabe -- 1973-1993.; Conflit israélo-arabe -- 1993-; Israël -- Politique et gouvernement.; Israël -- Frontières.; HISTORY -- General.; POLITICAL SCIENCE -- Colonialism & Post-Colonialism.; Arab-Israeli conflict; Boundaries; Military occupation; Politics and government; Zionism; Israel; Since 1967; History